Prospects for plant productivity: from the canopy to the nucleus - Gonzalez, Fernanda Gabriela; Manavella, Pablo A. (Oxford University Press, 2021)
Population growth has been closely associated with agricultural production, since the first famine predicted by Malthus (1798) up to the Green Revolution of the past century. Today, we continue to face increasing demand for food and crop production (Tilman et al., 2011). Considering the combined caloric or protein content of the 275 major crops used directly as human foods or as livestock and fish feeds, Tilman et al. (2011) forecast a 100% increase in global demand for crops from 2005 to 2050. Meeting this demand with the lowest impact on the environment could be achieved by sustainable intensification of existing cropland with reduced land clearing (Tilman et al., 2011; Fischer and Connor, 2018).